Disability Related to Self - care management among patients with Chronic Lymphatic filariasis in Kerala, India - Muttappallymyalil, J; Marickar, YMF; Elizabeth, KE; Sreedharan, J (Nepal Journal of Epidemiology, 2015)
Background Disability in self-care is a part of physical domain and is described as the inability to withstand bodily disruptions in normal functional performance. This study was conducted to determine the pattern of self-care management in patients with chronic lymphatic filariasis and to determine the disability in self-care on the basis of gender, duration of disease and stage of the disease in Kerala. Materials and Methods This cross-sectional study was conducted from 2008 to 2009 among individuals suffering from chronic lymphatic filariasis in Kannur District, Kerala State, India. 200 individuals with chronic lymphatic filariasis participated in this research. An interviewer-administered questionnaire, which had structured closed-ended questions and semi-structured open-ended questions, was used for data collection. A door-to-door survey was conducted to recruit the required sample size. Data analysed using SPSS version 21. Results In the present study 200 individuals (151 females and 49 males) with chronic lymphatic filariasis were participated. The mean age observed was 58.8 years with a minimum of 25 years and a maximum of 85 years. The factors included under self-care were bathing, grooming, dressing, and bowel and bladder management. The severity of self-care management shows that more than 60% had no difficulty in any of the self-care activities. 40% reported having at least some problem in toileting. Among the total participants, 3.5% reported extreme difficulty in bathing, followed by 1% in grooming, 1% in dressing and 1% in toileting. Some degree of bowel management problems was reported by 61.5% participants, and 67.5% had bladder management problems. Though males and females experienced bladder problems, former experienced them more. In both the groups the median score observed for bathing, grooming, dressing and toileting was ‘none’. There was no statistically significant difference in the median score observed between males and females. The leading difficulties related to self-care experienced by participants with duration of disease greater than 40 years were toileting (72.7%), bathing 39.4%, grooming 9.1%, and dressing (3.0%). Both bowel and bladder management problems were experienced by 85% of the participants having duration of disease greater than 40 years whereas 2.6% each experienced extremely severe bladder and bowel management problems. Statistically significant difference in median score was observed in bathing (p<0.05), grooming (p<0.05), Toileting (p<0.05) and bowel management (p<0.05), which shows as the duration of the disease increases; the difficulty for self-care management also increases. Maximum respondents with difficulty in toileting were in stage seven, the intensity ranged from a little to a lot. All distributions were statistically not different except for self-care related to toileting (p<0.05). Conclusion: The prevalence of difficulty in self-care management showed variations between the genders, duration of the disease and stage of the disease. DOI: http://dx.doi.org/10.3126/nje.v5i1.12375